Annotation and curation of hypothetical proteins: prioritizing targets for experimental study - Muhammad Naveed; Zoma Chaudhry; Zeeshan Ali; Mahnoor Amjad; Fizza Zulfiqar; Ali Numan (Advancements in Life Sciences, 2018)
Completely sequenced organisms have some uncharacterized proteins that are gene-encoded products. These proteins can be predicted through in-silico approaches and their biological activities are not proved by experimental evidence and known as hypothetical proteins (HPs). These proteins are important due to their excessive involvement in different cellular and signaling pathways. Structural and functional characterization of HPs reveal crucial roles in microorganisms, especially in pathogens related to human diseases. Here, we discussed all possibilities of in-silico analysis tools and other recently reported methods for hypothetical protein characterization and biomedical applications, including drug and vaccine development. Different methodologies, including meta-proteomics have been used to study protein expression by identification of HPs and comparative genomics have also come under observation due to the emergence of evolutionary study among different organisms. Structural characterization of proteins acts as a base for their functional prediction, novel drug target identification for disease treatment, vaccine production and sero-diagnosis. HPs have played major roles in different vital phenomenon for life including host adaptation, wound healing and chemotaxis. In the current era of drug and antibiotic resistance, HPs can be novel targets to treat related diseases. Identification and characterization of most HPs are under observation and will be the most promising genomic and bioinformatics techniques in structure-based drug designing and vaccine production in future.